2013
DOI: 10.3855/jidc.2576
|View full text |Cite
|
Sign up to set email alerts
|

ELISA seroprevalence of Trypanosoma cruzi in a cohort of heart disease patients

Abstract: Introduction: Chagas disease is the most important parasitic disease in El Salvador and Latin America. The disease has two phases: acute and chronic, with an intermediate unspecified phase. The chronic phase develops in 30% of infected persons and its most common manifestation is cardiac disease. This study aimed to obtain reference data for the prevalence of T. cruzi seropositivity in a cohort of cardiac patients. Methodology: A cross-sectional study involving consecutive heart disease patients consulting at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The results were similar to those of a previous study of 455 El Salvadorans who had been diagnosed with heart disease at the national tertiary hospital in 2010 [35]. Specifically, the study results indicated a significant association between T. cruzi seropositivity (16.7%) and residence in the Western region during childhood and youth.…”
Section: Discussionsupporting
confidence: 81%
“…The results were similar to those of a previous study of 455 El Salvadorans who had been diagnosed with heart disease at the national tertiary hospital in 2010 [35]. Specifically, the study results indicated a significant association between T. cruzi seropositivity (16.7%) and residence in the Western region during childhood and youth.…”
Section: Discussionsupporting
confidence: 81%
“…ECG abnormalities were more prevalent in the patients with ChD than in the seronegative patients, and this has been consistently demonstrated in many studies [7][8][9][10][11][12][13] . A retrospective observational study assessed 264,324 primary-care patients including 7,590 self-reported patients with ChD.…”
Section: Prevalence Of Electrocardiographic Alterationsmentioning
confidence: 71%
“…This interpretation is supported by an earlier study that reported a significant association between seropositivity and residence in the Western region during childhood and youth (Rodriguez et al . ).…”
Section: Discussionmentioning
confidence: 97%